Geostationary Orbit Slot Reconceptualization In Accommodating the South - Putro, Yaries Mahardika; Nugraha, Ridha Aditya; Nugraha, Taufik Rachmat (Indonesian Journal of International Law, 2022)
Geostationary Orbit (GSO) located above the equator is deemed as limited resources with strategic position for satellites in outer space. As today, the majority who possess GSO slots are non-equatorial states, in this context developed countries. The distribution of orbital slots in the GSO has been discussed among scholars from the developing states for decades. In the past, the developing states ever formed the “Bogota Declaration” aimed to ensure the developing states possess special rights over the GSO slot. The declaration arose from the distribution of the GSO slot by unequal treatment and dissatisfaction to the International Telecommunication Union (ITU) in global governance context. Concurrently the distribution of the GSO slot is based on a first-come-first-serve basis, recalling satellite technology development in the developing states is crawling; in contrast with developed states in which their satellite technologies are snowballing. This fact commonly disadvantages the developing states in many ways, they have an enormous risk of potential satellite re-entry as an accident for the developing states, equatorial states, and they have limited access to put their satellite above their skies. This article strives to provide recommendation that GSO slot distribution should lead to an unorthodox approach, namely to ensure developing countries have equal rights to GSO. The findings of this study argue that the current international space law regime is excessively “western-centric” and fails in accommodating developing countries’ interests. The special and differential treatment principle could serve as a basis for granting special rights to developing countries to utilize the GSO.